Promoting problem - based learning in learning engineering courses at Universiti Teknologi Malaysia - Khairiyah Mohd. Yusof, 1965-, author; Zaidatun Tasir, 1972-, author; Jamalludin Harun, 1971-, author; Syed Ahmad Helmi Syed Hassan, 1964-, author; Asia-Pacific Forum on Engineering and Technology Education (4th: 2005: Bangkok, Thailand) (Skudai : Universiti Teknologi Malaysia, 2005)
PSZJBL